A Liquid‐Metal–Elastomer Nanocomposite for Stretchable Dielectric Materials. Issue 23 (18th April 2019) - Pan, Chengfeng; Markvicka, Eric J.; Malakooti, Mohammad H.; Yan, Jiajun; Hu, Leiming; Matyjaszewski, Krzysztof; Majidi, Carmel
Abstract: Stretchable high‐dielectric‐constant materials are crucial for electronic applications in emerging domains such as wearable computing and soft robotics. While previous efforts have shown promising materials architectures in the form of dielectric nano‐/microinclusions embedded in stretchable matrices, the limited mechanical compliance of these materials significantly limits their practical application as soft energy‐harvesting/storage transducers and actuators. Here, a class of liquid metal (LM)–elastomer nanocomposites is presented with elastic and dielectric properties that make them uniquely suited for applications in soft‐matter engineering. In particular, the role of droplet size is examined and it is found that embedding an elastomer with a polydisperse distribution of nanoscale LM inclusions can enhance its electrical permittivity without significantly degrading its elastic compliance, stretchability, or dielectric breakdown strength. In contrast, elastomers embedded with microscale droplets exhibit similar improvements in permittivity but a dramatic reduction in breakdown strength. The unique enabling properties and practicality of LM–elastomer nanocomposites for use in soft machines and electronics is demonstrated through enhancements in performance of a dielectric elastomer actuator and energy‐harvesting transducer. Abstract : A liquid‐metal (LM)–elastomer nanocomposite is presented as a stretchable dielectric material. This material's architecture shows a unique combination of enhanced electric permittivity, controlled dielectric breakdown strength, and rubber‐like mechanical properties. These properties enable LM–elastomer nanocomposites to have potentially transformative impact on soft materials actuation, energy storage, and energy harvesting.